Signaling-induced systematic repression of miRNAs uncovers cancer vulnerabilities and targeted therapy sensitivity - Wurm, Alexander Arthur; Brilloff, Silke; Kolovich, Sofia; Schäfer, Silvia; Rahimian, Elahe; Kufrin, Vida; Bill, Marius; Carrero, Zunamys I.; Drukewitz, Stephan; Krüger, Alexander; Hüther, Melanie; Uhrig, Sebastian; et al. (Cell reports. Medicine, 2023)
Targeted therapies are effective in treating cancer, but success depends on identifying cancer vulnerabilities. In our study, we utilize small RNA sequencing to examine the impact of pathway activation on microRNA (miRNA) expression patterns. Interestingly, we discover that miRNAs capable of inhibiting key members of activated pathways are frequently diminished. Building on this observation, we develop an approach that integrates a low-miRNA-expression signature to identify druggable target genes in cancer. We train and validate our approach in colorectal cancer cells and extend it to diverse cancer models using patient-derived in vitro and in vivo systems. Finally, we demonstrate its additional value to support genomic and transcriptomic-based drug prediction strategies in a pan-cancer patient cohort from the National Center for Tumor Diseases (NCT)/German Cancer Consortium (DKTK) Molecularly Aided Stratification for Tumor Eradication (MASTER) precision oncology trial. In conclusion, our strategy can predict cancer vulnerabilities with high sensitivity and accuracy and might be suitable for future therapy recommendations in a variety of cancer subtypes.
Gesehen am 16.04.2024